Retraction notice to “Systematic green synthesis of silver oxide nanoparticles for antimicrobial activity” [Environ. Res. 202 (2021) 111627] - M. Mani; R. Harikrishnan; P. Purushothaman; S. Pavithra; P. Rajkumar; S. Kumaresan; Dunia A. Al Farraj; Mohamed Soliman Elshikh; Balamuralikrishnan Balasubramanian; K. Kaviyarasu (Environmental Research, 2026)

Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Three decades of livestock-relevant heat stress intensification along the Indian West Coast: a gridded THI trend and temperature-humidity contribution analysis - Subhradip Bhattacharjee; R. Solomon Rajkumar; V. Paramesha; Parveen Kumar; Basavareddy; Amitava Panja; Subham Singha; Dipak Dey; Prasanna Pal; Rakesh Kumar; Dinesh Kumar (Theoretical and Applied Climatology, 2026)

Development of subtropically-adapted indeterminate gametophyte1 (ig1) gene-based paternal haploid inducer lines in maize through molecular breeding - Amitkumar D. Kyada; Vignesh Muthusamy; Rashmi Chhabra; Botta T. Ganesh; Gulab Chand; Gaurav Sharma; Hriipulou Duo; Govinda R. Sarma; Ravindra K. Kasana; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Planta, 2026)

Functional characterization of cultivable endophytic bacteria from wild cotton Gossypium aridum and exploration of potent strain as seed bio-priming agent - Preeti R. Parmar; B.K. Rajkumar; Nitin Varshney; Diya Patel (Biocatalysis and Agricultural Biotechnology, 2026)

Correction to: Dynamics of accumulation of lysine and tryptophan, and kernel modification in opaque2, opaque16, and double mutant (opaque2/opaque16) genotypes during kernel development in maize - Gulab Chand; Vignesh Muthusamy; Tanu Allen; Nisrita Gain; Bhavna Singh; Suman Dutta; Nitish R. Prakash; Sohini Singh; Konsam Sarika; Gautam Chawla; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2026)

Hierarchical SPEES nanocomposite ionomer with phosphomolybdic acid decorated Co3O4 nanofiller as PEM for microbial fuel cells: An anti-biofouling and scale-up approach - John Solomon; Akshaya Senthilkumar; Naveen Rajkumar Sivakumar; R. Devi; Sangeetha Dharmalingam (Journal of Environmental Management, 2026)

Discovery of putative G-protein-biased µ-opioid agonists via hierarchical virtual screening of ultra-large chemical space - Rajkumar R; Tanmaykumar Varma; Prabha Garg (Molecular Diversity, 2026)

Long-term Conservation Agriculture with Subsurface Nitrogen Placement Enhances Wheat yield, Soil Nitrogen retention, and Nitrogen Use Efficiency in the North-west Indo-Gangetic Plains - Kiranmoy Patra; C. M. Parihar; Ayan Sarkar; K. Srikanth Reddy; D. R. Sena; Rajkumar Dhakar; Sneha Bharadwaj; Alok Sinha; Susnigdha Sengupta; Manojit Chowdhury; Hüdaverdi Gürkan; Hari Sankar Nayak (International Journal of Plant Production, 2026)

Drain, gain and sustain waterlogged-saline lands: assessing the impact of sub-surface drainage in India for policy perspectives - Suresh Kumar; Satyendra Kumar; Pratap Singh Birthal; Ranjay K. Singh; Rajkumar; Bhupender; Rohtash Kumar; Anil Kumar; R. K. Yadav (Environment, Development and Sustainability, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Dynamics of accumulation of lysine and tryptophan, and kernel modification in opaque2, opaque16, and double mutant (opaque2/opaque16) genotypes during kernel development in maize - Gulab Chand; Vignesh Muthusamy; Tanu Allen; Nisrita Gain; Bhavna Singh; Suman Dutta; Nitish R. Prakash; Sohini Singh; Konsam Sarika; Gautam Chawla; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2025)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

Groundwater usage characterization in a tribal stretch infected with chronic kidney disease of unknown etiology (CKDu) - Herojeet Rajkumar; Rakesh K. Dewangan; Pradeep K. Naik; Janak R. Verma; Prabir K. Naik (Journal of Environmental Sciences, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Behaviour of prestressed hollow core slabs after exposure to elevated temperatures: an experimental and numerical approach - T M Jeyashree; P R Kannan Rajkumar (Innovative Infrastructure Solutions, 2025)

Computational discovery of ATP-competitive GSK3β inhibitors using database-driven virtual screening and deep learning - Tanmaykumar Varma; Pradnya Kamble; R. Rajkumar; Prabha Garg (Molecular Diversity, 2025)

Effect of hybrid fiber and hybrid rebars on flexural strength of reinforced concrete beams - R. Rajkumar; Abhay Yadav; C. Arunkumar (Innovative Infrastructure Solutions, 2025)

Geochemical characterization of groundwater and source apportionment of potential pollutants in a tribal stretch infected with chronic kidney disease of unknown etiology - Herojeet Rajkumar; Pradeep K. Naik; Rakesh K. Dewangan; Janak R. Verma; Prabir K. Naik (Chemosphere, 2025)

UTF1 Expression is Important for the Generation and Maintenance of Human iPSCs - Khyati Raina; Kirti Modak; Chitra Premkumar; Gaurav Joshi; Dhavapriya Palani; Krittika Nandy; Yazhini Sivamani; Shaji R. Velayudhan; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2025)

Hydrogeochemical forecasting in a tribal stretch infected with chronic kidney disease of unknown etiology - Herojeet Rajkumar; Pradeep K. Naik; Rakesh K. Dewangan; Janak R. Verma; Prabir K. Naik (Science of The Total Environment, 2025)

Simplified mechanistic model for estimating leaf wetness - Rajkumar Dhakar; Basavaraj R. Amogi; Gajanan S. Kothawade; Lav R. Khot (Agricultural and Forest Meteorology, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Characterisation of 3D printing cake batter with xanthan gum and optimization of printing parameters using response surface methodology - Pentala Mallesham; S. Parveen; R. Pandiselvam; P. Rajkumar; Ravindra Naik (International Journal of Gastronomy and Food Science, 2024)

Seasonal variability of microplastic contamination in marine fishes of the state of Gujarat, India - Yagnesh B. Motivarash; Ashishkumar J. Bhatt; Rahul R. Jaiswar; Rehanavaz A. Makrani; Rajkumar M. Dabhi (Environmental Science and Pollution Research, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

Unraveling molecular architecture, development and validation of Anthocyanin1 gene-based novel breeder-friendly markers for utilization in genomics-assisted breeding of blue maize - Gaurav Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Govinda Rai Sarma; Deepak R. Sapkal; Firoz Hossain (South African Journal of Botany, 2024)

DeepNNet 15 for the prediction of biological waste to energy conversion and nutrient level detection in treated sewage water - T. Sathish; A. Vijayalakshmi; Raviteja Surakasi; N. Ahalya; M. Rajkumar; R. Saravanan; Sumarlin Shangdiar; Thandiwe Sithole; Kassian T.T. Amesho (Process Safety and Environmental Protection, 2024)

Insights into the population dynamics of phytophthora species associated with arecanut fruit rot disease - V.H. Prathibha; Balanagouda Patil; M.K. Rajesh; Sunil S Gangurde; M.N. Maruthi; K.P. Gangaraj; Thava Prakasa Pandian R; Daliyamol; M. Chaithra; Rajkumar; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2024)

Distinct mechanisms are responsible for E. coli biofilm desorption upon T4 coliphage infection and nutrient deprivation - Tammy R. Johnson; Kennedi A. Armstrong; Bliss N. Broussard; Raj Boopathy; Rajkumar Nathaniel; John Doucet; Jonathan Willis; Himanshu S. Raje (Bioresource Technology Reports, 2024)

Jamun Seed-Derived Nitrogen-Doped Carbon Dots: A Novel Microwave-Assisted Synthesis for Ultra-Bright Fluorescence and Mn7+ Detection - R. Swathi; G. Bhagavanth Reddy; Bandi Rajkumar; Dadigala Ramakrishna; P. Yadagiri Swamy (Journal of Fluorescence, 2024)

Effect of hybrid steel fibres on shear behaviour of self compacting RC beam - K. B. Ramkumar; C. Sudha; K. Gunasekaran; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Study on cyclic behavior of concrete column steel beam connections - Madhu Paudel; C. Arunkumar; R. Rajkumar (Innovative Infrastructure Solutions, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Long-term tributyltin exposure alters behavior, oocyte maturation, and histomorphology of the ovary due to oxidative stress in adult zebrafish - Rajkumar S. Delvadiya; Urvesh D. Patel; Mihir R. Tank; Harshad B. Patel; Swati S. Patel; Bhavesh J. Trangadia (Reproductive Toxicology, 2024)

Zinc solubilization and organic acid production by the entomopathogenic fungus, Metarhizium pingshaense sheds light on its key ecological role in the environment - C.M. Senthil Kumar; Sharon D'Silva; R. Praveena; Anees Kaprakkaden; L.R. Athira Krishnan; M. Balaji Rajkumar; V. Srinivasan; R. Dinesh (Science of The Total Environment, 2024)

Studies on the concrete with composite cement and alccofine: from use of OPC towards low-carbon quaternary binder - B. Suresh; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Drone remote sensing of wheat N using hyperspectral sensor and machine learning - Rabi N. Sahoo; R. G. Rejith; Shalini Gakhar; Rajeev Ranjan; Mahesh C. Meena; Abir Dey; Joydeep Mukherjee; Rajkumar Dhakar; Abhishek Meena; Anchal Daas; Subhash Babu; Pravin K. Upadhyay; et al. (Precision Agriculture, 2024)

Whole genome sequencing of bacteriophage NINP13076 isolated against Salmonella enteritidis - R Naveen Kumar; Ashok Selvaraj; Tamilzhalagan Sembulingam; Virendra Panpatil; Kaliaperumal Venkatesh; S.D.G. Gowthami; Uday kumar Putchaa; Uma Devi Ranganathan; Hemalatha Rajkumar; Sudip Ghosh; Ramalingam Bethunaickan (Ecological Genetics and Genomics, 2024)

Metal Contamination of Different Water Categories and Surface Soil Near Thermal Power Plants at Varied Geographic Sites of India and Their Health Risk Assessment - Khaiwal Ravindra; Nitasha Vig; Neha Agarwal; Vivek Singh Malik; Elangovan Arumugam; Prabu Rajkumar; Elavarasu Govindasamy; Punita Kumar; Prabir Chatterjee; Ramachandra Kamath; Surekha R Kamath; Sharvanan E. Udayar; et al. (Water, Air, & Soil Pollution, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

Nano-graphitic crystallites effect on the improved K-ion intercalation properties of Kigelia Africana fruit-derived hard carbon for potassium-ion batteries - N. Prasanna Naga Puneeth; K. Rajkumar; A. Soundarya; S.D. Kaushik; Yun Sung Lee; Sangho Park; R. Kalai Selvan (Chemical Engineering Journal, 2024)

Reproductive biology of green tiger shrimp Penaeus semisulcatus De Haan, 1844 in Palk Bay, southeast coast of India - M. Rajkumar; S. Lakshmi Pillai; P. Rameshkumar; R. Saravanan; S. Thirumalaiselvan; Josileen Jose; K.S. Sobhana; M. Rosalind George (Regional Studies in Marine Science, 2023)

Textile effluents decolourization potential of metal tolerant Aspergillus species and optimization of biomass concentration and temperature - Tan Phat Chau; R. Rajkumar; Abeer S Aloufi; Ramakrishnan Krishnan; Shan Ahamed Tharifkhan (Environmental Research, 2023)

A Review on Pyrolysis of Agro-waste and Plastic Waste into Biofuels: Shifting to Bio-based Economy - Midhun Prasad K; Murugavelh Somasundaram; B Anand; R Shankar; Rajkumar P (BioEnergy Research, 2023)

Bioremediation efficiency of free and immobilized form of Aspergillus niger and Aspergillus tubigenesis biomass on tannery effluent - Tan Phat Chau; Laura Bulgariu; Mythili Saravanan; R. Rajkumar; Arunachalam Chinnathambi; Saleh H. Salmen; G.K. Jhanani (Environmental Research, 2023)

Evaluation of Effect of Tapping Frequency and Lime Coating on the Biochemical Changes and Fermentation Rate of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; R. Pandiselvam (Sugar Tech, 2023)

Effect of packaging materials and storage temperature on the physicochemical and microbial properties of ultrasonicated mature coconut water during storage - Anjitha Jacob; I.P. Sudagar; R. Pandiselvam; P. Rajkumar; M. Rajavel (Food Control, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Mechanical properties and bond behaviour of steel rebar and fly ash–slag based geopolymer concrete in pull-out test - T. Srividya; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2023)

Correction to: Pollen staining is a rapid and cost‑effective alternative to marker‑assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Effect of mineral admixtures on mechanical and thermal properties of geopolymer mortar at elevated temperature - J. Baskara Sundararaj; P. R. Kannan Rajkumar; M. Sivasakthi; M. Jegan (Innovative Infrastructure Solutions, 2022)

Economic feasibility of subsurface drainage (SSD) to control waterlogging and soil salinity under different scenarios in the Tungabhadra project command, Karnataka, India - Karegoudar A V; Vishwanath J; Rajkumar R H; Anand S R; Polisgowdar B S; Ayyanagowdar M S; Nemichandrapp M; Kaledhonkar M J (Irrigation and Drainage, 2022)
The Tungabhadra irrigation command area (TBP) in Karnataka, India, has three scenarios: the head, mid and tail reach command areas. The head reach has ample good quality canal water availability, and the mid reach area has limited canal water availability. In recent decades, rice–rice monocropping in vertisols, especially by these head and mid reach farmers, has led to not only water shortages but also the development of waterlogging and secondary soil salinization in the tail (lower) reach of the command due to seepage. As the soil salinity in the head reach was less severe, a slightly wider drain spacing of 60 m was adopted over 15 ha. In the case of the mid reach, salinity was slightly higher than the head reach but slightly less than the tail reach, hence 50 m drain spacing was laid out over 24 ha. Due to the slightly higher soil salinity at the tail end of the command, a closer drain spacing of 40 m was adopted over 11 ha. In all these scenarios, the drain depth was 1.0 m. Despite differences in irrigation water availability and different soil salinity conditions, the study clearly indicated over six seasons that the SSD system is a viable solution for the reclamation of waterlogged saline soils and enhancing rice productivity in all three scenarios of the TBP command.

Pollen staining is a rapid and cost-effective alternative to marker-assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Methane emissions from dairy farms: case study from a coastal district in South India - Govind Pradeep; C. S. Shaijumon; R. Rajkumar; Jayadev Pradeep (Environment, Development and Sustainability, 2022)

Correction to: Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

First record of Fusarium falciforme (FSSC 3 + 4) a relevant human pathogen causing root decay of arecanut, Areca catechu L - R. Thava Prakasa Pandian; Shivaji Hausrao Thube; Babu Merin; V. H. Pratibha; M. Rajkumar; Priyank Hanuman Mhatre; Vinayaka Hegde (Journal of Plant Diseases and Protection, 2022)

Natural regeneration potential of Andaman Padauk (Pterocarpus dalbergioides) in sustaining the tropical forests of Andaman & Nicobar Islands, India - Iyyappan Jaisankar; R. Jayakumara Varadan; Bosco Augustine Jerard; Ganguly Nabanita; Muthu Rajkumar; Ayyam Velmurugan; S. K. Zamir Ahmed; Ezekiel Manasseh Moses (European Journal of Forest Research, 2022)

Efficacy of Clonal Propagation in Andaman Padauk ( Pterocarpus dalbergioides ): Augmenting Conservation of an Endemic Ornamental Timber Species of Andaman & Nicobar Islands, India - Iyyappan Jaisankar; R Jayakumara Varadan; S Vijayakumar; Nitiprasad Namdeorao Jambhulkar; Bosco Augustine Jerard; Nabanita Ganguly; Muthu Rajkumar; Ezekiel Manasseh Moses; Putcha Simhachalam (Forest Science, 2021)
The population of Andaman padauk (Pterocarpus dalbergioides Roxb.), an endemic ornamental timber species, is fast depleting in the Andaman Islands. Afforestation through seedlings is hindered by low germination and high mortality rates. This study attempts to assess the efficacy of clonal propagation methods to hasten mass multiplication by trying out different combinations of growth hormones, concentration, and dipping duration in semi-hardwood stem cuttings and different combinations of growth hormone concentration and substrate in air layering. Dipping the cuttings in indole-3-butyric acid (IBA) 1,500 ppm for 24 hours and spraying the modified stem-cut layers with IBA 2,000 ppm and binding with top soil and decomposed coir dust turned out to be the best treatment combination for cutting and air layering, respectively. Among the considered factors, the concentration of growth hormone is crucial for cutting, as the performance is enhanced with concentration under a given growth hormone and dipping duration. Similarly, the substrate is crucial for air layering, as modified stem-cut air layers bound with top soil and decomposed coir dust not only achieve the best performance, but also catalyze IBA for further improvement when other substrates remain unresponsive. Successful outcome of both clonal propagation techniques gives hope for disseminating the species across the tropics at global level.

Quantification of greenhouse gas emissions from managed biofuel plantations in a semi-arid landscape of Southern India - G. R. Rao; P. Sathi Reddy; M. Rajkumar (Tropical Ecology, 2021)

Allelic variation in sugary1 gene affecting kernel sweetness among diverse-mutant and -wild-type maize inbreds - Rashmi Chhabra; Vignesh Muthusamy; Nisrita Gain; Ashvinkumar Katral; Nitish R. Prakash; Rajkumar U. Zunjare; Firoz Hossain (Molecular Genetics and Genomics, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Inheritance of growth traits and impact of selection on carcass and egg quality traits in Vanashree, an improved indigenous chicken - Santosh Haunshi; Rajkumar U.; C. Paswan; L. L. L. Prince; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

A novel leaf rust resistance gene introgressed from Aegilops markgrafii maps on chromosome arm 2AS of wheat - K. Rani; B. R. Raghu; S. K. Jha; Priyanka Agarwal; Niharika Mallick; M. Niranjana; J. B. Sharma; A. K. Singh; N. K. Sharma; S. Rajkumar; S. M. S. Tomar; Vinod (Theoretical and Applied Genetics, 2020)

Morphological characterization and analysis of genetic diversity and population structure in Citrus × jambhiri Lush. using SSR markers - M. R. Rohini; M. Sankaran; S. Rajkumar; K. Prakash; A. Gaikwad; R. Chaudhury; S. K. Malik (Genetic Resources and Crop Evolution, 2020)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Development of microsatellite markers and their use in genetic diversity and population structure analysis in Casuarina - A. R. K. Kullan; A. V. Kulkarni; R. Suresh Kumar; R. Rajkumar (Tree Genetics & Genomes, 2016)

Response of upland cotton (G.hirsutum L.) genotypes to drought stress using drought tolerance indices - Chandrakant Singh; Vijay Kumar; Indivar Prasad; Vishal R. Patil; B. K. Rajkumar (Journal of Crop Science and Biotechnology, 2016)

Yield Enhancement Through Fertilizer Placement by Machine Below the Seed in Rain-fed Soybean Crop Under Vertisols - Devvrat Singh; Rajkumar Ramteke; I. R. Khan (Agricultural Research, 2016)

Estimation of Sea Ice Freeboard from SARAL/AltiKa Data - Megha Maheshwari; C. Mahesh; Kamaljit Singh Rajkumar; J. Pallipad; D. Ram Rajak; Sandip R. Oza; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Prospective biomarkers of stem cells of human endometrium and fallopian tube compared with bone marrow - S. Indumathi; R. Harikrishnan; J. S. Rajkumar; D. Sudarsanam; M. Dhanasekaran (Cell and Tissue Research, 2013)

Plasticity and banking potential of cultured adipose tissue derived mesenchymal stem cells - M. Dhanasekaran; S. Indumathi; R. Poojitha; A. Kanmani; J. S. Rajkumar; D. Sudarsanam (Cell and Tissue Banking, 2013)

Cx43, ZO-1, alpha-catenin and beta-catenin in cataractous lens epithelial cells - Anshul I Arora; Kaid Johar; Devarshi U Gajjar; Darshini A Ganatra; Forum B Kayastha; Anuradha K Pal; Alpesh R Patel; S Rajkumar; Abhay R Vasavada (Journal of Biosciences, 2012)

Rapid Real-Time PCR Assay for Culture and Tissue Identification of Geomyces destructans: the Etiologic Agent of Bat Geomycosis (White Nose Syndrome) - Sudha Chaturvedi; Robert J. Rudd; April Davis; Tanya R. Victor; Xiaojiang Li; Kim A. Appler; Sunanda S. Rajkumar; Vishnu Chaturvedi (Mycopathologia, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

First record of three giant marine Bathynomids (Crustacea, Isopoda, Cirolanidae) from India - R. Sankar; M. Rajkumar; Jun Sun; A. Gopalakrishnan; T. M. Vasanthan; G. Ananthan; J. P. Trilles (Acta Oceanologica Sinica, 2011)

Differential expression of Toll-like receptor mRNA in White Leghorn and indigenous chicken of India - Kannaki T. Ramasamy; Maddula R. Reddy; Dhanutha N. Raveendranathan; Shanmugam Murugesan; Rudra N. Chatterjee; Rajkumar Ullengala; Santosh Haunshi (Veterinary Research Communications, 2010)

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India - R. K. Sharma; M. S. Negi; S. Sharma; P. Bhardwaj; R. Kumar; E. Bhattachrya; S. B. Tripathi; D. Vijayan; A. R. Baruah; S. C. Das; B. Bera; R. Rajkumar; et al. (Biochemical Genetics, 2010)

High Level of Genetic Diversity Among the Selected Accessions of Tea (Camellia sinensis) from Abandoned Tea Gardens in Western Himalaya - S. Karthigeyan; S. Rajkumar; R. K. Sharma; Ashu Gulati; R. K. Sud; P. S. Ahuja (Biochemical Genetics, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Plant species diversity along an altitudinal gradient of Bhabha Valley in western Himalaya - Amit Chawla; S. Rajkumar; K. N. Singh; Brij Lal; R. D. Singh; A. K. Thukral (Journal of Mountain Science, 2008)

Type 1 (11; 22)(q24: q12) translocation is common in Ewing’s sarcoma/ peripheral neuroectodermal tumour in south Indian patients - T. Parija; S. Shirley; S. Uma; K. R. Rajalekshmy; S. Ayyappan; T. Rajkumar (Journal of Biosciences, 2005)

Characterization of a Novel Cr6+ Reducing Pseudomonas sp. with Plant Growth–Promoting Potential - M. Rajkumar; R. Nagendran; Kui Jae Lee; Wang Hyu Lee (Current Microbiology, 2005)

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

Molecular characterization of some Indian Basmati and other elite rice genotypes using fluorescent-AFLP - R. Aggarwal; V. Shenoy; J. Ramadevi; R. Rajkumar; L. Singh (Theoretical and Applied Genetics, 2002)

Leads to cancer control based on cancer patterns in a rural population in South India - R. Rajkumar; R. Sankaranarayanan; A. Esmi; R. Jayaraman; J. Cherian; D.M. Parkin (Cancer Causes & Control, 2000)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)